POLITICAL ASPECTS OF THE AZERBAIJANI-BRITISH RELATIONSS (International relations and international law Journal, 2016)
This article deals with the analysis of existent politicalrelations between Great Britain and Azerbaijan. The authorapproached this problem from the historical prism. This articleanalysed the historical roots of their relations. It was noted that Great Britain is one of the first countries recognizing theindependence of Azerbaijan. The interests of the both stateswere duly researched in the established relations. At the end of the article the author paid special attention to the activity ofAzerbaijani Diaspora in England. The article investigates theactivity of each organizations acting in this country of Behalf ofAzerbaijan.
Keywords: Azerbaijani-British relations; foreign policy